Marketing Training Through Social Media in Increasing Sales of MSME Products in Tanggulangin Sidoarjo - Nanik Hariyana; G. Oka Warmana (Future Science, 2022)
A Based on initial observations in Kedensari RT.17 RW.05 there is a Home Industry driven by MSMEs that produce handicrafts and bags. However, the business is still underdeveloped in terms of: 1) Product Marketing Activities 2) Limited marketing, 3) Marketing distribution channels whose reach is still limited 4) Business management that is not well organized. Therefore the Pikat Team seeks to provide knowledge transfer in the form of how to make product development and increase product diversity and diversification as well as how to packaging that has a certain appeal and branding in order to attract consumers as well as opportunities to be marketed to various MSME areas in Kedensari RT.17 RW.05. With a solution to the problems faced by the MSME group in Kedensari RT.17 RW.05, Tanggulangin, Sidoarjo, Pikat has the following objectives: 1) Improve quality through the use of supporting production process equipment 2) Increase food added value and producer income through variety and product diversification, 3) increasing the reach of product marketing distribution channels 4) Providing knowledge transfer on business management. Implementation method with: focus group discussion, demonstration and practice or exercise. The output targets resulting from the activity are: 1) Improving the quality and quantity of products produced 2) The use of online marketing. 3) Increased marketing activities that can increase sales 4) Improved business management with better financial records and business activities.